SISTEM INFORMASI PENJUALAN SECARA ONLINE (Studi Kasus Pada CV. Java Mini Semarang) - Andik Susdiyanto; Danang Danang (Universitas Sains dan Teknologi Komputer, 2018)
The development of information technology is currently growing very rapidly along with the discovery and development of knowledge in the field of information and communication so as to create tools that support the development of information technology, ranging from communication systems that are unidirectional and two-way (interactive). Every machine that is able to receive data, process data, store data, and produce output in the form of text, symbols, numbers and sounds can be categorized as a computer. CV. Java Mini Semarang is well aware of the importance of information technology for the smooth running of its business. Fast and accurate information is needed by the company in making decisions in the field of product promotion offered. Promotional media using brochures at this time are still experiencing problems, because of the limited delivery of information in terms of information about the latest products and product prices offered by the company, so it requires a lot of time and is less efficient. To overcome the problems in the CV. Java Mini Semarang needs new promotional media which is faster and more accurate in conveying information, this new promotional media is expected to complement the old promotional media that still uses brochures. Promotional media using brochures are still considered to be lacking because the scope is less extensive. And one of the media that can provide information quickly, accurately and a very broad reach is to use website media.Based on the description above in the preparation of this thesis, the author takes the title